High-thermal-conductivity ultra-low-specific-gravity thermal pad and preparation method thereof

CN122978714APending Publication Date: 2026-10-27ZHONGKE HEAT TECH JIANGSU CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610814199.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-08
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但该类填料表面活性基团有限,与聚合物基体之间界面相容性较差,易发生团聚,难以在基体中形成均匀、连续的导热网络;同时,其导热性能具有明显的方向性,在厚度方向上的导热提升效果有限,导致整体导热效率受限,难以稳定实现高导热与低比重的协同

Benefits of technology

[0016]本发明通过对导热填料体系及界面结构进行协同设计,在保证高导热性能的同时实现了材料的超低比重与良好力学性能的统一。具体而言,通过对六方氮化硼进行特定酸性条件下的表面处理,显著改善其在有机硅基体中的分散性与界面相容性,有利于构建连续稳定的导热通路,从而在较低填充密度下获得较高的导热系数;同时,引入中空玻璃微珠在不破坏导热网络的前提下降低体系整体密度,并缓解填料间刚性接触带来的应力集中,使导热垫片兼具轻量化、柔韧性及结构稳定性。由此,本发明有效解决了现有导热垫片中高导热与高比重难以兼顾的问题,适用于对散热效率和轻量化均具有较高要求的应用场景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a high-thermal-conductivity ultra-low-specific-gravity thermal-conductivity gasket and a preparation method thereof. The thermal-conductivity gasket takes an organic silicon polymer as a matrix, introduces surface-treated hexagonal boron nitride and hollow glass microbeads, and builds a continuous thermal-conductivity network through interface synergistic control, so that the material specific gravity is significantly reduced while the thermal conductivity coefficient is relatively high, and good flexibility and structural stability are achieved, and the thermal-conductivity gasket is suitable for fields such as electronic devices which have relatively high requirements for efficient heat dissipation and light weight.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of thermal pads, and in particular to a high thermal conductivity, ultra-low specific gravity thermal pad and its preparation method. Background Technology

[0002] With the rapid development of electronics, new energy, and aerospace, related equipment is evolving towards higher integration, higher power density, and miniaturization, significantly increasing the heat generated during operation. If this heat cannot be effectively conducted and dissipated from the heat source in a timely manner, the operating temperature of the device will rise, leading to performance degradation, decreased reliability, and even failure. Therefore, improving the heat dissipation efficiency of electronic devices has become one of the key factors restricting their performance and lifespan.

[0003] Thermal pads, as commonly used thermal interface materials, are typically placed between heat-generating elements and heat dissipation structures to fill microscopic gaps at the contact interface, reduce interfacial thermal resistance, and achieve rapid heat conduction. Existing high thermal conductivity thermal pads mostly use polymers as the matrix and fill them with high thermal conductivity inorganic fillers, such as alumina and aluminum nitride. By increasing the filler content, thermal conduction pathways are constructed, thereby achieving higher thermal conductivity.

[0004] However, the aforementioned high thermal conductivity fillers generally have high density. When the filler content is increased to achieve a thermal conductivity of ≥8W / (m·K), the overall specific gravity of the thermal pad increases significantly, typically above 3.0g / cm³. This not only increases the weight of the device but is also detrimental to applications with high lightweight requirements, such as aerospace and portable electronic devices. Furthermore, high filler content can easily lead to decreased material flexibility and poor interfacial adhesion, affecting actual performance.

[0005] To balance thermal conductivity and lightweight requirements, some existing technologies have attempted to introduce two-dimensional thermally conductive fillers such as graphene and hexagonal boron nitride to achieve high thermal conductivity with relatively low filler content. However, these fillers have limited surface active groups, poor interfacial compatibility with the polymer matrix, and are prone to agglomeration, making it difficult to form a uniform and continuous thermally conductive network in the matrix. Furthermore, their thermal conductivity exhibits a clear directionality, with limited improvement in thermal conductivity along the thickness direction, resulting in limited overall thermal conductivity efficiency and making it difficult to stably achieve a synergistic effect of high thermal conductivity and low specific gravity.

[0006] In addition, the introduction of lightweight fillers or multiphase composite structures into existing thermal pads often leads to problems such as insufficient interfacial bonding of the filler, powder shedding during long-term use, or decreased structural stability, which further limits their promotion in high-reliability application scenarios.

[0007] In summary, the existing technology still lacks a thermal pad and its preparation method that can achieve ultra-low material specific gravity while ensuring high thermal conductivity, and also take into account good flexibility, interfacial compatibility and usage stability. Summary of the Invention

[0008] This application provides a thermally conductive pad, comprising the following components by weight percentage: 30-45 parts of polymer matrix; 45-60 parts of hexagonal boron nitride; 5-10 parts of hollow glass microspheres; 2-5 parts of dispersant; 1-3 parts of adhesion accelerator; Crosslinking agent 0.5-2 parts; The catalyst is a platinum catalyst, and its addition amount is 0.001% to 0.003% of the polymer matrix mass, calculated at 5000 ppm. The inhibitor is an acetylene alcohol inhibitor, and its addition amount is 0.05 to 0.2% of the polymer matrix mass.

[0009] As a preferred technical solution for thermally conductive pads, the polymer matrix is ​​an organosilicon polymer.

[0010] As a preferred technical solution for thermally conductive pads, the organosilicon polymer is vinyl-terminated polydimethylsiloxane.

[0011] As a preferred technical solution for thermal pads, the hexagonal boron nitride is surface-treated boron nitride.

[0012] As a preferred technical solution for thermally conductive pads, the surface treatment is performed using an organosilicon coupling agent.

[0013] In addition, this application provides a method for preparing a thermally conductive pad, characterized by comprising the following steps: S1. Provide hexagonal boron nitride and perform surface treatment; S2. Mix the hexagonal boron nitride with hollow glass microspheres; S3. Mix the mixture obtained in step S2 with the polymer matrix, dispersant, adhesion promoter and crosslinking agent; S4. The mixture is molded and cross-linked to obtain a thermally conductive pad.

[0014] In a preferred embodiment of a method for preparing a thermally conductive pad, in step S1, the surface treatment is performed under conditions where the pH is 3 to 4.

[0015] In a preferred embodiment of a method for preparing a thermally conductive pad, in step S4, the molding is carried out at a temperature of 150–160°C.

[0016] This invention achieves a balance between ultra-low specific gravity and good mechanical properties by synergistically designing the thermally conductive filler system and interface structure, ensuring high thermal conductivity. Specifically, by subjecting hexagonal boron nitride to surface treatment under specific acidic conditions, its dispersibility and interfacial compatibility in the organosilicon matrix are significantly improved, facilitating the construction of continuous and stable thermal conductive pathways, thereby obtaining a high thermal conductivity at a low filler density. Simultaneously, the introduction of hollow glass microspheres reduces the overall density of the system without disrupting the thermally conductive network and alleviates stress concentration caused by rigid contact between fillers, resulting in a thermally conductive pad that is lightweight, flexible, and structurally stable. Therefore, this invention effectively solves the problem of balancing high thermal conductivity and high specific gravity in existing thermally conductive pads, making it suitable for applications requiring both high heat dissipation efficiency and lightweight design. Detailed Implementation

[0017] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.

[0018] Example 1

[0019] Components (by weight): Vinyl-terminated polydimethylsiloxane: 30 parts; Hexagonal boron nitride: 60 parts; Hollow glass microspheres: 5 parts; Dispersant (polyether-modified polydimethylsiloxane): 2 parts; Adhesion accelerator (γ-aminopropyltriethoxysilane): 1 part; Crosslinking agent (hydrogen-containing polydimethylsiloxane, hydrogen content 0.5 parts): 2 parts; The catalyst is a platinum catalyst, with an addition amount of 0.001% of the polymer matrix mass, calculated at 5000 ppm. The inhibitor is an acetylene alcohol inhibitor, and its addition amount is 0.2% of the polymer matrix mass.

[0020] Preparation method: S1. Surface Treatment: Take 60 parts of hexagonal boron nitride for later use. Dissolve 0.6 parts of vinyltrimethoxysilane in a mixed solvent of 200 parts of ethanol / deionized water (volume ratio 9:1), adjust the pH to 3.5 with glacial acetic acid, and stir magnetically for 30 min to ensure complete hydrolysis of the coupling agent. Add boron nitride to the above solution and react with stirring in a 60℃ constant temperature water bath for 4 h. After the reaction is complete, filter, wash the filter cake three times with ethanol (100 parts each time), and dry under vacuum at 120℃ for 4 h to obtain surface-treated boron nitride.

[0021] S2. Powder premixing: 60 parts of surface-treated boron nitride and 5 parts of hollow glass microspheres are put into a high-speed disperser and mixed at 1500 rpm for 15 min.

[0022] S3. Slurry preparation: Add 30 parts of vinyl-terminated polydimethylsiloxane, 2 parts of dispersant, 1 part of adhesion promoter, 2 parts of crosslinking agent, catalyst, and inhibitor to the above powder in sequence. Place in a planetary mixer, evacuate to -0.1 MPa, and stir for 40 min until a bubble-free, uniform paste slurry is obtained.

[0023] S4. Molding and Crosslinking: Pour the slurry into a mold preheated to 150℃ with a thickness of 2mm, hot press and crosslink for 30 minutes. After naturally cooling to room temperature, demold to obtain a thermally conductive pad with a thickness of 2mm.

[0024] Example 2

[0025] Components (by weight): Vinyl-terminated polydimethylsiloxane: 45 parts; Hexagonal boron nitride: 45 parts; Hollow glass microspheres: 5 parts; Dispersant (polyether-modified polydimethylsiloxane): 2 parts; Adhesion accelerator (γ-aminopropyltriethoxysilane): 1 part; Crosslinking agent (hydrogen-containing polydimethylsiloxane, hydrogen content 0.5 parts): 2 parts; The catalyst is a platinum catalyst, and its addition amount is 0.003% of the polymer matrix mass, calculated at 5000 ppm. The inhibitor is an acetylene alcohol inhibitor, and its addition amount is 0.05% of the polymer matrix mass.

[0026] Preparation method: S1. Surface Treatment: Take 45 parts of hexagonal boron nitride for later use. Dissolve 0.45 parts of vinyltrimethoxysilane in 200 parts of ethanol / deionized water (9:1), adjust the pH to 3.5 with glacial acetic acid, and stir for 30 min for hydrolysis. Add boron nitride, stir at 60℃ for 4 h, filter, wash 3 times with ethanol, and dry under vacuum at 120℃ for 4 h.

[0027] S2. Powder premixing: 45 parts of surface-treated boron nitride + 5 parts of glass microspheres are mixed in a high-speed disperser at 1500 rpm for 15 min.

[0028] S3. Slurry preparation: Add 45 parts polymer, 2 parts dispersant, 1 part adhesion promoter, 2 parts crosslinking agent, catalyst and inhibitor, and stir in a planetary mixer at -0.1MPa vacuum for 40 minutes until uniform and bubble-free.

[0029] S4. Molding and cross-linking: Pour into a 2mm mold preheated to 150℃, hot-press cross-linking for 35 minutes, and then cool and demold.

[0030] Example 3

[0031] Components (by weight): Vinyl-terminated polydimethylsiloxane: 36.5 parts; Hexagonal boron nitride: 45 parts; Hollow glass microspheres: 10 parts; Dispersant (polyether-modified polydimethylsiloxane): 5 parts; Adhesion accelerator (γ-aminopropyltriethoxysilane): 3 parts; Crosslinking agent (hydrogen-containing polydimethylsiloxane, hydrogen content 0.5 parts): 0.5 parts; The catalyst is a platinum catalyst, with an addition amount of 0.002% of the polymer matrix mass, calculated at 5000 ppm. The inhibitor is an acetylene alcohol inhibitor, and its addition amount is 0.1% of the polymer matrix mass.

[0032] Preparation method: S1. Surface treatment: Take 45 parts of hexagonal boron nitride. Dissolve 0.45 parts of vinyltrimethoxysilane in 200 parts of ethanol / water (9:1), hydrolyze at pH=3.5 for 30 min, add boron nitride and react at 60℃ for 4 h, filter and wash 3 times, and vacuum dry at 120℃ for 4 h.

[0033] S2. Powder premixing: 45 parts of treated boron nitride + 10 parts of glass microspheres, high speed mixing at 1500 rpm for 15 min.

[0034] S3. Slurry preparation: Add 36.5 parts polymer, 5 parts dispersant, 3 parts adhesion promoter, 0.5 parts crosslinking agent, catalyst and inhibitor, and stir under vacuum at -0.1MPa for 40 minutes using a planetary mixer.

[0035] S4. Molding and cross-linking: Pour into a 2mm mold preheated to 160℃, hot-press cross-link for 25 minutes, and then cool and demold.

[0036] Example 4

[0037] Components (by weight): Vinyl-terminated polydimethylsiloxane: 40 parts; Hexagonal boron nitride (D50=75μm): 50 parts; Hollow glass microspheres (D50=60μm): 5 parts; Dispersant (polyether-modified polydimethylsiloxane): 2 parts; Adhesion accelerator (γ-aminopropyltriethoxysilane): 2 parts; Crosslinking agent (hydrogen-containing polydimethylsiloxane, hydrogen content 0.5 parts): 1 part; The catalyst is a platinum catalyst, with an addition amount of 0.001 wt% of the polymer matrix, calculated at 5000 ppm. The inhibitor is an acetylene alcohol inhibitor, and its addition amount is 0.15 wt% of the polymer matrix.

[0038] Preparation method: S1. Surface treatment: Take 50 parts of hexagonal boron nitride. Dissolve 0.5 parts of vinyltrimethoxysilane in 200 parts of ethanol / water (9:1), adjust the pH to 3.5 with glacial acetic acid, stir for 30 min to hydrolyze, add boron nitride and react at 60℃ for 4 h, filter, wash 3 times with ethanol, and vacuum dry at 120℃ for 4 h.

[0039] S2. Powder premixing: 50 parts of treated boron nitride + 5 parts of glass microspheres, mixed in a high-speed disperser at 1500 rpm for 15 min.

[0040] S3. Slurry preparation: Add 40 parts polymer, 2 parts dispersant, 2 parts adhesion promoter, 1 part crosslinking agent, catalyst and inhibitor, and stir under vacuum of -0.1MPa for 40 minutes in a planetary mixer until no bubbles are present.

[0041] S4. Molding and cross-linking: Pour into a 2mm mold preheated to 152℃, hot-press cross-link for 30 minutes, and then cool to room temperature for demolding.

[0042] Compare with Example 1 Compared with Example 1, the only difference is that hollow glass microspheres were not added, and the 5 parts by mass percentage were added to hexagonal boron nitride (i.e., hexagonal boron nitride becomes 65 parts, and hollow glass microspheres become 0 parts). The proportions of other components, particle size and all preparation methods (S1 to S4, including surface treatment pH=3.5, organosilicon coupling agent, etc.) are exactly the same.

[0043] Compare with Example 2 Compared with Example 1, the only difference is that no surface treatment is performed in step S1, and hexagonal boron nitride without any treatment is used directly. The proportions of other components, particle size and all preparation methods (S2 to S4) are exactly the same.

[0044] Compare with Example 3 Compared with Example 1, the only difference is that in step S1, the pH is adjusted to 7 (neutral condition) with glacial acetic acid during surface treatment, while the proportions of other components, particle size, and all preparation methods (S2 to S4, including the continued use of vinyltrimethoxysilane) are exactly the same.

[0045] Performance testing methods 1. Thermal conductivity (unit: W / m·K): According to ASTM D5470 standard, the gasket sample is sandwiched between two parallel metal plates, and the temperature gradient and heat flow are measured under steady-state heat flow to calculate the thermal conductivity. 2. Density (unit: g / cm³): According to ASTM D792 standard, the mass of the sample in air and water (or in a liquid of known density) is measured by the displacement method or a hydrometer, the volume is calculated and the density is obtained.

[0046] 3. Tensile strength (unit: MPa): Prepare dumbbell-shaped specimens according to ASTM D412 standard, stretch them at 500 mm / min on a universal testing machine until fracture, and calculate the maximum stress at fracture.

[0047] 4. Elongation at break (unit: %) In accordance with ASTM D412, during the tensile test described above, the elongation of the specimen from its initial length to the point of fracture is measured and the percentage is calculated.

[0048] Table 1

[0049] As can be seen from Examples 1 to 4 and Table 1, the thermally conductive pad of the present invention can stably achieve a thermal conductivity of 8.2 to 10.3 W / (m·K), while the material density is controlled at 1.32 to 1.52 g / cm³. 3 Within a relatively low range, its thermal conductivity is significantly lower than that of traditional high thermal conductivity filled thermal pads; furthermore, its tensile strength remains between 1.60 and 2.10 MPa, and its elongation at break remains between 155 and 180%, indicating that while achieving synergistic optimization of high thermal conductivity and low specific gravity, the material still possesses good mechanical integrity and flexibility. This demonstrates that the present invention achieves a comprehensive balance between thermal conductivity, lightweight, and reliability through specific component ratios and interface control.

[0050] Combining Example 1, Comparative Example 1, and Table 1, it can be seen that under the condition that the thermally conductive filler system and preparation process are basically the same, the thermal conductivity of Comparative Example 1, due to the absence of hollow glass microspheres, is slightly improved, but the material density is significantly increased, while the tensile strength and elongation at break are significantly decreased. This indicates that simply increasing the content of high-density thermally conductive filler can enhance the thermal conductivity pathway, but it will lead to an increase in the overall specific gravity of the material, an increase in the rigidity of the system, and a reduction in flexibility. In contrast, the introduction of hollow glass microspheres in Example 1 effectively reduces the average density of the system without disrupting the continuity of the boron nitride thermal conductive network, and alleviates the rigid contact between fillers through the spatial support effect of the microspheres, thereby significantly improving the lightweight level and mechanical compatibility of the material while maintaining high thermal conductivity.

[0051] As can be seen from Example 1, Comparative Example 2, and Table 1, when hexagonal boron nitride is directly introduced into the organosilicon matrix without surface treatment, its thermal conductivity, tensile strength, and elongation at break all show a significant decrease. This is because the surface polarity of untreated boron nitride has poor compatibility with the organosilicon matrix, easily leading to agglomeration and the formation of thermal resistance and stress concentration zones at the interface, resulting in discontinuous thermal conductivity pathways and insufficient interfacial bonding. In contrast, Example 1 uses an organosilicon coupling agent to surface-treat boron nitride, introducing functional structures that can chemically or physically entangle with the matrix, thereby significantly improving filler dispersion and interfacial bonding, which is beneficial for constructing a continuous and stable thermally conductive network and simultaneously improving the mechanical properties of the material.

[0052] As can be seen from Example 1, Comparative Example 3, and Table 1, under the same conditions using organosilicon coupling agents, the thermal conductivity and mechanical properties of Comparative Example 3, when surface treated under neutral pH conditions, are lower than those of Example 1. This indicates that the hydrolysis and condensation reactions of the coupling agent are significantly dependent on the reaction environment. Under weakly acidic conditions with a pH of 3-4, the coupling agent can be fully hydrolyzed and uniformly anchored on the boron nitride surface, thereby forming a stable and effective interfacial transition layer. However, under neutral conditions, the hydrolysis and condensation reactions are insufficient, resulting in limited interfacial modification effects, which in turn weakens the interfacial heat transfer and stress transmission capabilities between the filler and the matrix, ultimately affecting the overall thermal conductivity and structural stability.

[0053] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A thermally conductive pad, characterized in that, By weight percentage, it includes the following components: 30-45 parts of polymer matrix; 45-60 parts of hexagonal boron nitride; 5-10 parts of hollow glass microspheres; 2-5 parts of dispersant; 1-3 parts of adhesion accelerator; Crosslinking agent 0.5-2 parts; The catalyst is a platinum catalyst, and its addition amount is 0.001 to 0.003% of the polymer matrix mass, calculated at 5000 ppm. The inhibitor is an acetylene alcohol inhibitor, and its addition amount is 0.05 to 0.2% of the polymer matrix mass.

2. The thermally conductive pad according to claim 1, characterized in that, The polymer matrix is ​​an organosilicon polymer.

3. The thermally conductive pad according to claim 2, characterized in that, The organosilicon polymer is vinyl-terminated polydimethylsiloxane.

4. The thermally conductive pad according to claim 1, characterized in that, The hexagonal boron nitride is a surface-treated boron nitride.

5. The thermally conductive pad according to claim 4, characterized in that, The surface treatment is performed using an organosilicon coupling agent.

6. A method for preparing a thermally conductive pad as described in any one of claims 1 to 5, characterized in that, Includes the following steps: S1. Provide hexagonal boron nitride and perform surface treatment; S2. Mix the hexagonal boron nitride with hollow glass microspheres; S3. Mix the mixture obtained in step S2 with the polymer matrix, dispersant, adhesion promoter and crosslinking agent; S4. The mixture is molded and cross-linked to obtain a thermally conductive pad.

7. The preparation method according to claim 6, characterized in that, In step S1, the surface treatment is performed under conditions of pH 3 to 4.

8. The preparation method according to claim 7, characterized in that, In step S4, the molding is carried out at 150-160°C.